Shape preserving chemical transformation of ZnO mesostructures into anatase TiO2 mesostructures for optoelectronic applications - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Yengantiwar, Ashish; Ogale, Satishchandra B. (Energy & Environmental Science, 2011)
In this work we report on the synthesis of various ZnO mesostructures (rods, spheres, flakes and flower-like morphologies) by hydrothermal and co-precipitation methods and their remarkable and complete transformation into anatase TiO2 mesostructures with nominally similar shapes using controlled low temperature TiCl4 treatment. Various techniques are used to demonstrate the phase purity and morphology details. Based on the careful examination of the transformation of ZnO rods into TiO2 tubes we suggest a mechanism which embodies initial formation of a thin TiO2 shell on the ZnO surface by ion exchange (Ti4+-Zn2+) followed by Zn diffusion through the shell and its oxidation on the surface. We used these converted TiO2 mesostructures for light harvesting in Dye Sensitized Solar Cells (DSSCs) to enhance the conversion efficiency. It is shown that DSSCs made using a doctor bladed film of TiO2 nanoparticles with an overlayer of TiCl4 treated ZnO flowers yield a solar cell efficiency of 6.9% which is considerably higher than that with only TiO2 nanoparticle film (5.4%) of comparable thickness.